2011
DOI: 10.1017/s0007114511004843
|View full text |Cite
|
Sign up to set email alerts
|

The whey fermentation product malleable protein matrix decreases TAG concentrations in patients with the metabolic syndrome: a randomised placebo-controlled trial

Abstract: Animal and human studies suggest that a malleable protein matrix (MPM) from whey decreases plasma lipid concentrations and may positively influence other components of the metabolic syndrome such as glucose metabolism and blood pressure (BP). The primary objective of this double-blind, multi-centre trial was to investigate the effects of a low-fat yoghurt supplemented with whey MPM on fasting TAG concentrations in patients with the metabolic syndrome. A total of 197 patients were randomised to receive MPM or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 63 publications
1
25
2
Order By: Relevance
“…In our recent review, we identified 4 RCTs and a pilot study that evaluated the long-term effects of dairy proteins on lipid metabolism (50). Our results are in agreement with the majority of these studies (5153); however, we failed to detect a decrease in LDL cholesterol or an increase in HDL cholesterol. Longer supplementation periods with milk proteins may have been more informative on the relative effects of dairy proteins on other lipid profiles or on the strength of significance.…”
Section: Discussionsupporting
confidence: 93%
“…In our recent review, we identified 4 RCTs and a pilot study that evaluated the long-term effects of dairy proteins on lipid metabolism (50). Our results are in agreement with the majority of these studies (5153); however, we failed to detect a decrease in LDL cholesterol or an increase in HDL cholesterol. Longer supplementation periods with milk proteins may have been more informative on the relative effects of dairy proteins on other lipid profiles or on the strength of significance.…”
Section: Discussionsupporting
confidence: 93%
“…Dairy proteins have potential to suppress postprandial lipaemia due to their insulinotropic effects, as insulin is known to inhibit hormone-sensitive lipase and release of FFA [62]. However, studies on the effects of milk protein ingestion on postprandial lipaemia and chronic dyslipidaemia have produced mixed findings [63-70]. Two studies in healthy normolipaemic young men and women reported that 50 g sodium caseinate suppressed the postprandial response following a 70 g fat bolus, decreasing diet-derived chylomicrons and FFAs independent of gastric emptying, compared to an oligosaccharide bolus [64,65].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of metabolic syndrome, a significant decrease in fasting TG was demonstrated following a 3 month period of supplementation of 15 g/day of a fermented whey product, whey malleable protein matrix (MPM, comprising whey proteins, peptides, a probiotic, polysaccharides and calcium) [70], as were other risk factors but only in individuals with high pre-existing metabolic risk. Metabolic outcomes in this study may have been driven by weight loss since body weight also decreased following MPM supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…After a full-text review of the remaining 21 potentially relevant articles, 12 articles were further excluded because they used milk other than whey and its derivates as the intervention products (three articles), measured an acute effect (two articles), did not report the CRP data (five articles) or had no control group (two articles). Finally, nine RCTs were selected for our meta-analysis [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%